Technology Transfer, Investment and Indonesian Patent Law - Hutauruk, Dwi Eryka Happy Kusuma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
In 2020, Indonesia has just revised the local working provision contained in Article 20 of Law no. 13 of 2016 concerning Patents through the ratification of Law no. 11 of 2020 concerning Job Creation. According to the Government of Indonesia in the Academic Paper of the Draft Law on Amendments to Law Number 13 of 2016 concerning Patents, the main reason for the revision of this article is because it will hinder foreign investment from entering Indonesia and also violates Article 27 (1) TRIPs which contains the prohibition on foreign investment. discrimination. This article will try to argue that the imposition of local working in Article 20 of the 2016 Patent Law obligations does not violate TRIPs and the local working provisions in the Patent Law must be maintained.